IMPLEMENTATION OF THE POLICE CODE OF ETHICS FOR POLICE OFFICERS IN PALOPO POLICE STATION - Ichsan, Nursyamsi; Attas, Nasrah Hasmiati; Syam, Andi Fatmawaty (International Journal of Business, Law, and Education, 2022)
The Police Code of Ethics aims to try to put Police Ethics in a proportional manner in relation to society. The number of cases of violations of the code of ethics committed by members of the Police makes the public image of the Police diminish and even seem to assume that members of the Police are immune to the law, because many cases involving police officers just disappear and evaporate before reaching the trial. This study aims to determine the implementation of the Police Code of Ethics and analyse the factors that influence the occurrence of violations of the Police Code of Ethics in the Palopo police station. The research method used in this research is normative-empirical legal research with deductive data analysis techniques. The findings of this research elucidate that the application of the Police Code of Ethics among members of the Indonesian National Police, as stipulated in Law Number 2 of 2002, does not align with the legal regulations. In conclusion, the study reveals that the reasons behind violations of the Polri code of ethics are intricately linked to five factors, namely the legal factor, the law enforcement apparatus factor, the supporting facilities for the law enforcement process, community factors, and cultural factors. The Government of the Republic of Indonesia should exercise prudence in administering sanctions against Police personnel who breach the code of ethics.